Infrared-to-visible CW frequency upconversion in erbium activated silica-hafnia waveguides prepared by sol-gel route - Goncalves, R. R.; Carturan, G.; Zampedri, L.; Ferrari, M.; Chiasera, A.; Montagna, M.; Righini, G. C.; Pelli, S.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2003)
70SiO(2)-30HfO(2) mol% planar waveguides, doped with Er3+ with concentrations ranging from 0.3 to 2 mol% were prepared by sol-gel route, using dip-coating deposition on vitreous-SiO2 substrates. Infrared-to-visible upconversion emission, upon excitation at 980 nm, has been observed for all the samples. The upconversion results in green, red and blue emissions. The investigation of the upconversion dynamic as a function of the Er3+ concentration and excitation power, show that processes such as excited state absorption and energy transfer upconversion are effective. (C) 2003 Elsevier B.V. All rights reserved.